New challenges in heart failure - Davidson, Christopher (Eesti Arst, 2003)
Heart failure has received much publicity in the last five years. In all western countries, the numbers of patients admitted to hospital with heart failure is rising sharply. There is now widespread agreement about the poor prognosis, which is worse than many forms of cancer (1). Heart failure has also become, rather belatedly, a topic of considerable interest for cardiologists. As well as new drugs available, there are increasingly sophisticated procedures involving biventricular pacing and the use of defibrillators which, though costly, can significantly improve prognosis in certain patient groups (2).